2007
DOI: 10.1002/jccs.200700184
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Pyrido[2,3‐d]Pyrimidine‐2‐Thiones and a Study of Their Reactivity Towards Some Reagents

Abstract: A series of pyrido[2,3‐d]pyrimidine‐2‐thione derivatives (5a‐c) were synthesized by the one‐pot reaction of the appropriate aldehyde, malononitrile and 6‐aminothiouracil (1) in dimethyl‐formamide. The same compounds were also synthesized by the reaction of arylidine malononitrile (4) with 6‐aminothiouracil (1). Moreover, the chemical behaviour of the produced pyrimidines towards different reagents was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…This spirocycloadduct was reported to undergo further rearrangement reaction in situ to produce the triazolo [1,2,4][4,3-a]pyrimidine derivatives by removal of hydrogen sulfide. [28,31] It is noteworthy that the survey in the literature [28,[31][32][33][34] revealed that N 3 -nitrogen atom (not N 1 -nitrogen atom) was involved in the cyclization to afford the structure 17, not the isomer [35] 17′ that was explained by the plane of symmetry of structure 17 rather than its isomer 17′, which lacks this symmetry [34] (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…This spirocycloadduct was reported to undergo further rearrangement reaction in situ to produce the triazolo [1,2,4][4,3-a]pyrimidine derivatives by removal of hydrogen sulfide. [28,31] It is noteworthy that the survey in the literature [28,[31][32][33][34] revealed that N 3 -nitrogen atom (not N 1 -nitrogen atom) was involved in the cyclization to afford the structure 17, not the isomer [35] 17′ that was explained by the plane of symmetry of structure 17 rather than its isomer 17′, which lacks this symmetry [34] (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it reacted with hydrazonylhalide derivative 25 in ethanol containing little amount of triethylamine to afforded the triazolopyrimidine derivative 26 or the isomeric structure 27. We believe that the structure 26 is the correct one because it has the plane of symmetry than the structure 27 which has not this symmetry [21]. The structure 26 was established based on the compatible elemental analysis and spectroscopic data.…”
Section: Resultsmentioning
confidence: 99%
“…The structure 26 was established based on the compatible elemental analysis and spectroscopic data. The formation of 26 was assumed to proceed according to the mechanism described in scheme 6 as reported in literature [21].…”
Section: Resultsmentioning
confidence: 99%
“…[18] Consequently, a number of synthetic approaches have been reported for the preparation of pyrido [2,3d]pyrimidine derivatives. [19][20][21][22] Moreover, the literature survey reveals that pyrido [2,3-d]pyrimidines are usually synthesized by condensation of aromatic aldehyde, malononitrile, and 6-aminouracil or its derivatives at different reaction conditions such as 1) tetra-n-butyl ammonium bromide (TBAB)/ ultrasonic irradiation/water/70°C/50 min; [23] 2) triethylbenzylammonium chloride (TEBAC)/water/90°C/6-10 h; [24] 3) nanocrystalline MgO/water/80°C/12-35 min; [25] 4) KF-Al 2 O 3 /ethanol/90°C/5-8 h; [26] 5) diammonium hydrogen phosphate (DAHP)/water-ethanol/reflux/2 h; [27] 6) DMF/reflux/ 20-30 h; [28] 7) NaBr/ethanol or acetonitreile/electrolysis/25-30 min; [29] 8) SBA-Pr-SO 3 H/solvent free/5-45 min; [30] 9) Al-HMS-20/ethanol/RT/12 h [31] ; and 10) thiamine hydrochloride/water/90°C/2-2.5 h. [32] By considering the pharmacological significance of pyrido [2,3d]pyrimidines and within the framework of green chemistry approach for the expansion of our previous success, [33] we herein report a clean, efficient, and ecofriendly protocol for the glycerolassisted catalyst-free synthesis of pyrido[2,3-d]pyrimidine derivatives by one-pot three-component condensation of aromatic aldehyde, malononitrile, and 6-aminouracil or 6-amino-1,3dimethyluracil (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a number of synthetic approaches have been reported for the preparation of pyrido[2,3‐ d ]pyrimidine derivatives . Moreover, the literature survey reveals that pyrido[2,3‐ d ]pyrimidines are usually synthesized by condensation of aromatic aldehyde, malononitrile, and 6‐aminouracil or its derivatives at different reaction conditions such as 1) tetra‐ n ‐butyl ammonium bromide (TBAB)/ultrasonic irradiation/water/70 °C/50 min; 2) triethylbenzylammonium chloride (TEBAC)/water/90 °C/6‐10 h; 3) nanocrystalline MgO/water/80 °C/12‐35 min; 4) KF‐Al 2 O 3 /ethanol/90 °C/5‐8 h; 5) diammonium hydrogen phosphate (DAHP)/water‐ethanol/reflux/2 h; 6) DMF/reflux/20‐30 h; 7) NaBr/ethanol or acetonitreile/electrolysis/25‐30 min; 8) SBA–Pr–SO 3 H/solvent free/5‐45 min; 9) Al–HMS‐20/ethanol/RT/12 h; and 10) thiamine hydrochloride/water/90 °C/2‐2.5 h …”
Section: Introductionmentioning
confidence: 99%